KARAKTERISTIK DAN SKRINING FITOKIMIA EKSTRAK ETANOL 70% BATANG KEPUH (Sterculia foetida L.) - N. P. S. E. Cahyani; J. Susiarni; K. C.S. Dewi; N. L.P. Melyandari; K. W.A. Putra; D. A. Swastini (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2019)
Kepuh (Sterculia foetida L) is a type of kapok plant that has been scientifically proven to have activity as an anti-inflammatory and analgesic. 70% ethanol extract of stem stem is obtained by maceration using 70% ethanol. Examination of the characteristics of 70% ethanol extract of kepuh stem included organoleptic, of moisture content and determination of residual solvent content. Phytochemical screening of 70% ethanol extract of kepuh bark includes: alkaloid, flavonoid, saponin, tannin , polyphenol, and examination of glycosides. The results of the examination of the characteristics of 70% ethanol extract of kepuh stem obtained water content of 8.66 ± 0.748%, the residual content of the solvent had a 0 (zero) ethanol level. The results of phytochemical screening showed 70% ethanol extract of stem stem containing steroid compounds, triterpenoids, flavonoids, saponins, tannins and polyphenols. The identification using UV-Vis spectrophotometry produced ? 212, the absorbance was 1.8601 and ? 284, the absorbance was 0.42186.